Sosialisasi Bahaya Minuman Serbuk Bagi Kesehatan Pada Anak Sekolah Dasar Di Kecamatan Sukawati Kabupaten Gianyar Provinsi Bali - I Wayan Ambartana Ambartana; Ni Made Yuni Gumala Yuni Gumala (Jurnal Pengabmas Masyarakat Sehat, 2020)
ABSTRACT One of the artificial sweeteners used in powdered drinks is cyclamate. Cyclamate is a sodium salt of cyclamic acid with the molecular formula C6H11NHSO3Na. Sodium cyclamate tastes sweet without any unpleasant taste, is very easy to dissolve in water, and the sweetness intensity is about 30 times the sweetness of pure cane sugar.Cyclamate can endanger health, even though it has a high level of sweetness and tastes good (without bitter taste). The level of cyclamate poisoning in experimental mice is 50% of dead experimental animals; by mouth 12.0 g / kg body weight. Cyclamate is carcinogenic (can cause cancer) especially in the bladder.Research conducted by the Food and Drug Inspection Center in November to December shows that cyclamate consumption in primary school children has reached 24% of ADI (Acceptable Daily Intake) or Safe Daily Consumption. The effect of artificial sweeteners on humans did not materialize immediately. Artificial sweeteners will continue to accumulate and will be harvested after children grow up, because it can be said of silent disease.This Community Service was held in August 2019 with the target of grade 5 elementary school students in Ketewel Elementary School Number 6 and Guwang Elementary School Number 1 in Sukawati District, Gianyar Regency, totaling 45 people. Interference is given in the form of counseling. Evaluation is done by assessing the results of the pre test and post test. There was an increase in knowledge of 1.95 points compared to before, there was an increase in skills compared to before. There needs to be supervision of the school canteen manager, socialization of powder drinks by the authorities should be increased.